2002
DOI: 10.1021/om010770z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Interannular Bridge on Spectral and Electronic Properties of Bis(cyclopentadienyl)- and Bis(indenyl)zirconium(IV) Complexes

Abstract: Interconnection of the indenyl ligands of bis(indenyl)zirconium dichloride complexes by a 1,1‘-positioned Me2Si or (CH2)2 bridge causes pronounced bathochromic shifts of the longest wavelength UV/vis absorption bands by ca. 50 nm, while much smaller shifts are caused by a Me2Si bridge in otherwise analogous bis(cyclopentadienyl) complexes. Extended Hückel MO calculations show that overlap between the empty 4d orbitals of the ZrCl2 2+ fragment and the highest filled π orbitals of the indenyl anions is decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…However, a strong bathochromic shift can be combined with the almost unchanged electron density on the Zr atom as it was shown earlier [17].…”
Section: Introductionsupporting
confidence: 55%
“…However, a strong bathochromic shift can be combined with the almost unchanged electron density on the Zr atom as it was shown earlier [17].…”
Section: Introductionsupporting
confidence: 55%
“…Subsequent UV−vis studies on the supported systems indicated that light irradiation may, however, favor olefin coordination . UV−vis spectroscopy has been used to extensively study the activation of metallocenes in homogeneous solution and has recently been extended to silica-supported systems in an attempt to elucidate the interactions between the metal center and the monomer 81 or supported cocatalyst …”
Section: 4 Lights Camera Actionmentioning
confidence: 99%
“…Such a different behavior is likely due to a combination of steric and electronic effects since 1e4 are not only less encumbered than 5e6 [26] but they also bear most acidic metal centers [27]. Once the ZreN bond is formed, the CeH activation of one of the NMe groups of the amine leads to the formation of the zirconaziridinium structures 7e10.…”
Section: Cp* 2 Zrme 2 (5)mentioning
confidence: 99%